Ettore Sottsass architect and designer - Labaco, Ronald T.; Doordan, Dennis P.; Sparke, Penny; Steele, James; Zaiden, Emily (London New York Merrell : Los Angeles County Museum of Art, 2006)
Naast de objecten en het meubilair wordt ook zijn architectuur belicht.
Adlib record nr. 530009988
Published on the occasion of the exhibition 'Ettore Sottsass, Designer' organized by the Los Angeles County Museum of Art and made posssible by Max Palevsky. Exhibition dates: 12/03-11/06/2006.
Engels
Ettore Sottsass: architect and designer
kunstcatalogus
Keywords: Sottsass, Ettore; 20ste eeuw; Italië